Способ определения оптимальной скорости резания - Нестеренко В. П. Владимир Петрович; Арефьев К. П. Константин Петрович; Кондратюк А. А. Алексей Алексеевич; Меркулов В. И. Валерий Иванович; Сериков Л. В. Леонид Вениаминович
опубл. 27.02.02